Do caregivers’ involvement in Type 2 diabetes education affect patients’ health outcomes?: A systematic review and meta-analysis (Journal of Health Sciences, 2023)
Introduction: The prevalence of Type 2 diabetes mellitus (T2DM) is rising worldwide. Patients frequently struggle with controlling their diabetes and need the assistance of caregivers for effective self-management because managing diabetes requires a variety of strategies, including diet, glucose monitoring, and exercise. This study aimed to examine the effect of caregiver involvement in T2DM education within a community on patients’ diabetes care outcomes.Methods: Based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, a systematic review of all published studies from the earliest record to May 2022 that reported adult caregivers of T2DM patients who participated in educational interventions concerning diabetes management and that reported one or more outcomes of the interventions were conducted. Four databases were used, including PubMed, Cochrane Library, EMBASE, and CINAHL. The meta-analysis focused on glycated hemoglobin (HbA1c) levels among randomized controlled trials (RCTs), with additional attention to lipid levels. Review Manager 5.4 was used to perform this meta-analysis.Results: A total of 17 out of 683 studies were synthesized. Involvement of caregivers in T2DM education is shown to reduce body mass index and HbA1c. This involvement also improves patients’ knowledge, physical activity, and self-efficacy, but the effect on medication adherence varies. A meta-analysis of six RCT studies shows that caregiver involvement in T2DM education reduced pooled HbA1c levels by 0.83 (95% Confidence interval: −1.27–−0.38) compared to involvement (p = 0.0003). Meta-analysis of three types of lipids (low-density lipoprotein, total cholesterol, and high-density lipoprotein) showed no strong evidence that caregiver participation in diabetes education improved lipid levels.Conclusions: Caregivers play key roles in diabetes management and can contribute to improving patient HbA1c levels. Future research should focus on enhancing caregiver participation in T2DM education.